1984
DOI: 10.3109/00016348409154646
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Artery Lesions in Relation to Metabolic Control in Diabetes Mellitus

Abstract: Decidual and intramyometrial spiral arteries from 18 insulin-dependent diabetic and 18 non-diabetic women were compared histologically. All women were normotensive and none had signs of pre-eclampsia. None of the infants in either group had intra-uterine growth retardation. Metabolic control in the diabetic women was assessed by pregnancy glucose level from the last trimester of pregnancy and by C-peptide in amniotic fluid and cord blood as a measure of the fetal beta-cell function. The intramyometrial and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…They undergo remodeling during gestation, directed by natural maternal killer cells and invasive trophoblast lineages derived from embryos [14]. The present fi ndings were consistent with Bjork, et al, [13], whom reported two of the 18 diabetic patients showed Abnormal spiral artery was also detected in 69/203 of obese cases (33.9%) [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They undergo remodeling during gestation, directed by natural maternal killer cells and invasive trophoblast lineages derived from embryos [14]. The present fi ndings were consistent with Bjork, et al, [13], whom reported two of the 18 diabetic patients showed Abnormal spiral artery was also detected in 69/203 of obese cases (33.9%) [24].…”
Section: Discussionsupporting
confidence: 92%
“…Two of the 18 diabetic patients developed intramural fi brosis in the decidual portion of the spiral artery. Hyperglycaemia and abnormal level of C-peptide values in amniotic fl uid and cord blood had been infl uenced in the induction of spiral artery lesions [13] The Pomegranate fruit's peel, seeds and juice are rich in antioxidants Pomegranate (Punica granatum L.), Punica granatum Linn. (Family , Punicaceae ), is commonly known as pomegranate.…”
mentioning
confidence: 99%
“…The detailed mechanisms of placental responses also remain to be determined. This is a complex endeavor, because trophoblast invasion and, hence, spiral artery remodeling may be modified by maternal obesity (10) and diabetes (11).…”
Section: Early Pregnancymentioning
confidence: 99%
“…SA remodeling is thought to transform this arterial tree to a high capacity, low resistance conduit that is unresponsive to vasoactive substances and thus provides continuous placental perfusion. In human pregnancies complicated by diabetes, placental insufficiency is seen more frequently, implicating inadequate remodeling of SA [11,12].The NOD mouse is a well-established model of autoimmune T1DM that shares several diabetes-susceptibility genes with humans. NOD mice spontaneously develop overt diabetes after 12 weeks of age.…”
mentioning
confidence: 99%